2017
DOI: 10.3390/molecules22010136
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Several Docking Programs at Reproducing Protein–Macrolide-Like Crystal Structures

Abstract: The accuracy of five docking programs at reproducing crystallographic structures of complexes of 8 macrolides and 12 related macrocyclic structures, all with their corresponding receptors, was evaluated. Self-docking calculations indicated excellent performance in all cases (mean RMSD values ≤ 1.0) and confirmed the speed of AutoDock Vina. Afterwards, the lowest-energy conformer of each molecule and all the conformers lying 0–10 kcal/mol above it (as given by Macrocycle, from MacroModel 10.0) were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 53 publications
6
80
0
2
Order By: Relevance
“…Structure-based docking methods rank molecules via a scoring function that is calculated based on their inner methods (Yang et al, 2019). In addition, the previous study also showed that AutoDock Vina was a more efficient option for stimulating protein docking with macrolides and analogues of intermediate size ligand compared to other docking programs, such as Glide 6.6, AutoDock 4.2 and DOCK 6.5 (Castro-Alvarez et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Structure-based docking methods rank molecules via a scoring function that is calculated based on their inner methods (Yang et al, 2019). In addition, the previous study also showed that AutoDock Vina was a more efficient option for stimulating protein docking with macrolides and analogues of intermediate size ligand compared to other docking programs, such as Glide 6.6, AutoDock 4.2 and DOCK 6.5 (Castro-Alvarez et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A docked conformation with a smaller RMSD is considered as a more accurate solution to the docking problem. Compared CEPGA with GA, LGA, SODOCK, and ABC (Castro-Alvarez et al 2017 ; Feinstein and Brylinski 2015 ), Table 2 show that CEPGA has the best performance in the search for the lowest energy and the smallest RMSD of molecular docking conformations.…”
Section: Discussionmentioning
confidence: 99%
“…Glide offers the full range of speed vs. accuracy options, from the HTVS (high-throughput virtual screening) mode for efficiently enriching million compound libraries, to the SP (standard precision) mode for reliably docking tens to hundreds of thousands of ligand with high accuracy, and to the extra precision (XP) mode where further elimination of false positives is accomplished by more extensive sampling and advanced scoring, resulting in even higher enrichment. Many researchers carried out extensive comparisons of several docking programs and scoring functions using an extensive data set of pharmaceutically attractive targets and active compounds [13][14][15][16][17][18]. All the study leads to the same result that Glide XP methodology was shown to yield enrichments superior to the alternative methods consistently.…”
Section: Computationalmentioning
confidence: 98%